A comparative study on the law of homelessness in Malaysia and UK / Siti Qistina Azmi ... [et al.] - Azmi, Siti Qistina; Nordin, Nur Afiqah; Mohd Zulhaini, Nur Alwani; Raja Ismail, Raja Syuhadah Nur Hasanah (2013)
This research is about homelessness issue in Malaysia. Our topic is a comparative study on homeless people in Malaysia and UK. This means we compare the law between these two country and we look at how to improve the existing law in Malaysia. Homelessness is not the stereotype like what people think, there are much more factors that causing this issue to arise. There is much more behind the sad faces that people see on the streets. Homelessness is a critical issue that requires everyone's attention. Hundreds of thousands of homeless people live on the streets as their shelter. The objective of our research is to compare the laws regarding homelessness issue in the UK and in Malaysia itself. By doing this research, we have identified the key issues and what can be improvised in coping with this matter. In conclusion, in coping with this issue that has become more serious year by year, a new interventions and policy is needed to prevent homelessness.